MRI Evidence of Altered Callosal Sodium in Mild Traumatic Brain Injury - Grover, H.; Qian, Y.; Boada, F.E.; Lakshmanan, K.; Flanagan, S.; Lui, Y.W. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Mild traumatic brain injury is a leading cause of death and disability worldwide with 42 million cases reported annually, increasing the need to understand the underlying pathophysiology because this could help guide the development of targeted therapy. White matter, particularly the corpus callosum, is susceptible to injury. Animal models suggest stretch-induced mechanoporation of the axonal membrane resulting in ionic shifts and altered sodium ion distribution. The purpose of this study was to compare the distribution of total sodium concentration in the corpus callosum between patients with mild traumatic brain injury and controls using sodium (23Na) MR imaging.MATERIALS AND METHODS: Eleven patients with a history of mild traumatic brain injury and 10 age- and sex-matched controls underwent sodium (23Na) MR imaging using a 3T scanner. Total sodium concentration was measured in the genu, body, and splenium of the corpus callosum with 5-mm ROIs; total sodium concentration of the genu-to-splenium ratio was calculated and compared between patients and controls.RESULTS: Higher total sodium concentration in the genu (49.28 versus 43.29 mmol/L, P = .01) and lower total sodium concentration in the splenium (which was not statistically significant; 38.35 versus 44.06 mmol/L, P = .08) was seen in patients with mild traumatic brain injury compared with controls. The ratio of genu total sodium concentration to splenium total sodium concentration was also higher in patients with mild traumatic brain injury (1.3 versus 1.01, P = .001).CONCLUSIONS: Complex differences are seen in callosal total sodium concentration in symptomatic patients with mild traumatic brain injury, supporting the notion of ionic dysfunction in the pathogenesis of mild traumatic brain injury. The total sodium concentration appears to be altered beyond the immediate postinjury phase, and further work is needed to understand the relationship to persistent symptoms and outcome.CCcorpus callosummTBImild traumatic brain injuryTSCtotal sodium concentration